Do Patrimônio Imaterial às Populações Tradicionais Brasileiras - Pacheco de Souza Silva, Fabiana (2023)
The concepts of traditional knowledge and biodiversity have been associated due to the emergence of a new kind of knowledge: biotechnological. Biological systems have been used in the manufacture of pharmaceuticals, cosmetics, generating a new discussion in the Brazilian domestic law and the international system on the appropriation of traditional knowledge of indigenous peoples and the lack of distribution of profits. It is necessary to verify the protection of the intellectual property of the indigenous people, so that their rights to receive the aforementioned profits materialize, as explained in the TRIPS Agreement, since until them, the lack of a specific law in the Brazilian legal system for the protection of such knowledge and property, besides the gap in the TRIPS Agreement, have facilitated piracy, leaving unprot ected not only the indigenous, but also the Brazilian people.